2021
DOI: 10.48102/rlee.2021.51.2.384
|View full text |Cite
|
Sign up to set email alerts
|

Peace Education and Colombia’s Efforts Against Violence: A Literature Review of Cátedra de la Paz

Abstract: As long as there has been violence in organized societies, achieving peace has been a goal through different means, including education. In Colombia –a country where the national government and the guerrilla FARC reached a peace agreement–, education was set to be essential to promote a culture of peace. Accordingly, this article presents a literature review of Cátedra de la Paz, a peace education course that seeks to encourage and strengthen a culture of peace in every educational institution in Colombia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In Colombia—a country that still experiences chronic violence despite myriad efforts to counteract it (Avila Martínez, 2020; Rettberg, 2020)—the body of literature concerning civic education has mainly focused on ministerial and program-led efforts toward human rights, peaceful convivencia , 2 conflict resolution, values-driven conducts, and democratic school culture (Chaux et al, 2004; Cortés Salcedo, 2009; Mieles Barrera and Alvarado Salgado, 2012; Nieto and Bickmore, 2016; Nieto Sicacha, 2021; Restrepo, 2006; Ruíz Silva and Chaux, 2005). Attention has centered on the features and merits of the national citizenship competence program (Chaux et al, 2004), the increasing number of plans and strategies focused on students’ skills, moral and cognitive development for peace and democracy (Peláez and Márquez, 2006; Torres and Pinilla Díaz, 2005), and civic programs and curricular requirements concerning school climate, students’ socioemotional skills, interpersonal relations, and prevention of further aggressions (Chaux, 2007, 2009; Morales, 2021; Vásquez-Russi, 2020; Velásquez et al, 2017). However, scholarship has not fully engaged with the citizen as a key character, nor with the contingencies, struggles, and shaping forces that make civic education—and thus the citizen—intelligible and possible the way it is in the present.…”
Section: Education Conflict Complexity and The Formation Of Citizensmentioning
confidence: 99%
“…In Colombia—a country that still experiences chronic violence despite myriad efforts to counteract it (Avila Martínez, 2020; Rettberg, 2020)—the body of literature concerning civic education has mainly focused on ministerial and program-led efforts toward human rights, peaceful convivencia , 2 conflict resolution, values-driven conducts, and democratic school culture (Chaux et al, 2004; Cortés Salcedo, 2009; Mieles Barrera and Alvarado Salgado, 2012; Nieto and Bickmore, 2016; Nieto Sicacha, 2021; Restrepo, 2006; Ruíz Silva and Chaux, 2005). Attention has centered on the features and merits of the national citizenship competence program (Chaux et al, 2004), the increasing number of plans and strategies focused on students’ skills, moral and cognitive development for peace and democracy (Peláez and Márquez, 2006; Torres and Pinilla Díaz, 2005), and civic programs and curricular requirements concerning school climate, students’ socioemotional skills, interpersonal relations, and prevention of further aggressions (Chaux, 2007, 2009; Morales, 2021; Vásquez-Russi, 2020; Velásquez et al, 2017). However, scholarship has not fully engaged with the citizen as a key character, nor with the contingencies, struggles, and shaping forces that make civic education—and thus the citizen—intelligible and possible the way it is in the present.…”
Section: Education Conflict Complexity and The Formation Of Citizensmentioning
confidence: 99%
“…People's expectations about living peacefully with the surrounding environment did not work as they should. Several studies have shown that the lack of peace in individuals correlates with violence [7]- [9]. Research in Indonesia shows that the level of aggressiveness tends to increase in an undesirable direction [10]- [12].…”
Section: Introductionmentioning
confidence: 99%
“…People's expectations about living peacefully with the surrounding environment did not work as they should. Several studies have shown that the lack of peace in individuals correlates with violence [7], [8] and contributes to high levels of aggressive behavior [9]. Research in Indonesia shows that the level of aggressiveness of students in the very high category is 5.82%, and in the high category is 17.82% [10].…”
Section: Introductionmentioning
confidence: 99%